1998
DOI: 10.1520/jfs16219j
|View full text |Cite
|
Sign up to set email alerts
|

Criminal and Behavioral Aspects of Juvenile Sexual Homicide

Abstract: This preliminary research provides a descriptive, systematic study of juvenile sexual homicide. Fourteen incarcerated juveniles, identified through a department of corrections computer search, were assessed using a structured diagnostic interview, an author-designed clinical interview, and a review of correctional files and other available records. Five of the offenders' victims survived the homicidal attack, but their cases were nevertheless included in this study as the offenders' intent was clearly to kill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 14 publications
1
7
0
1
Order By: Relevance
“…Furthermore, this is the second study to apply the SADSEX‐SH to a juvenile sexual murder sample (Chopin & Beauregard, 2020 being the first), and it continued to show good diagnostic and psychometric properties, including a positive predictive value of 90%. The additional findings of family dysfunction and serious school problems in over 80% of the youth, and the low frequency of intellectual disability (5%) and a history of childhood sexual abuse (12%), were also in line with previous studies of JSHOs (Myers, 2002). Other noteworthy findings were torture and vaginal rape being perpetrated at the crime scenes by about half of the sample, and necrophilic and piqueristic acts committed by about a third of the offenders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, this is the second study to apply the SADSEX‐SH to a juvenile sexual murder sample (Chopin & Beauregard, 2020 being the first), and it continued to show good diagnostic and psychometric properties, including a positive predictive value of 90%. The additional findings of family dysfunction and serious school problems in over 80% of the youth, and the low frequency of intellectual disability (5%) and a history of childhood sexual abuse (12%), were also in line with previous studies of JSHOs (Myers, 2002). Other noteworthy findings were torture and vaginal rape being perpetrated at the crime scenes by about half of the sample, and necrophilic and piqueristic acts committed by about a third of the offenders.…”
Section: Discussionsupporting
confidence: 89%
“…Juvenile sexual homicide (JSH) is a complex phenomenon with biopsychosocial, familial, cultural, genetic, and evolutionary roots (Chan, 2017; Myers, 2002). While the number of studies on JSH has been slowly growing in recent decades, the limited research available remains hindered by small, questionably representative samples, given that JSHs comprise just about 10% of all sexual homicides (Myers, Chan, & Mariano, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jenkins (1992) found that multiple killings were frequently committed in conjunction with other serious crimes, such as abduction, rape, robbery, or residential burglary. Fortunately, a variety of investigators have examined the offending backgrounds of MHOs and found they generally have had official contacts with the criminal justice system (Myers, Burgess, & Nelson, 1998). For instance, Canter, Missen, and Hodge (1996) analyzed the offending backgrounds of 217 U.S. serial killers and found that 75% of them had previous convictions.…”
Section: Criminal Careers Of Mhosmentioning
confidence: 99%
“…[29] They rarely feel remorse for their actions competency. [20] and they deny offences or minimize the acts and the damage they inflict. Ferrara and McDonald [30] reported that almost one-third of ers with other violent and nonviolent juvenile offenders, found no juvenile sex offenders had some form of neurological impairment, significant difference regarding neuropsychological, intellectual, learning disability, or academic dysfunction.…”
Section: Behavior Pattern and Cognitive Andmentioning
confidence: 99%